Scanning Electrochemical Microscopy Imaging during Respiratory Burst in Human Cell - Kikuchi, Hiroyuki; Prasad, Ankush; Matsuoka, Ryo; Aoyagi, Shigeo; Matsue, Tomokazu; Kasai, Shigenobu (Frontiers in Physiology, 2016)
Phagocytic cells, such as neutrophils and monocytes, consume oxygen and generate reactive oxygen species (ROS) in response to external stimuli. Among the various ROS, the superoxide anion radical is known to be primarily produced by nicotinamide adenine dinucleotide phosphate hydrogen (NADPH) oxidase. In the current study, we attempt to evaluate the respiratory burst by monitoring the rapid consumption of oxygen by using scanning electrochemical microscopy (SECM) imaging. The respiratory burst was measured in a human monocytic cell line (THP-1 cells) derived from an acute monocytic leukemia patient under the effect of the exogenous addition of phorbol 12-myristate 13-acetate, which acts as a differentiation inducer. SECM imaging composed of a microelectrode was used to compare oxygen consumption between normal cellular respiration and during respiratory burst in THP-1 cells. Two-dimensional respiratory activity imaging was performed using XY-scan. In addition, the quantitative evaluation of oxygen consumption in THP-1 cells was performed using a Z-scan. The results obtained show higher consumption of oxygen in cells undergoing respiratory burst. SECM imaging is thus claimed to be a highly sensitive and appropriate technique compared to other existing techniques available for evaluating oxidative stress in human cells, making it potentially useful for widespread applications in biomedical research and clinical trials.